The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1079/ssr2004187
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the sensitivity of parasitic weed seeds to germination stimulants

Abstract: The effects of preconditioning temperature and preconditioning period on the sensitivity of parasitic weed seeds to the synthetic germination stimulant GR24 were studied under laboratory and field conditions. The temperature during preconditioning of Orobanche cumana and Striga hermonthica seeds strongly affected the responsiveness of the seeds to the applied germination stimulant. Preconditioning at an optimal temperature (21°C for O. cumana and 30°C for S. hermonthica) rapidly released dormancy and increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 33 publications
1
67
0
Order By: Relevance
“…gesnerioides seeds Ten milligrams of Striga seeds (approximately 1,500 seeds) was surface-sterilized according to the method of Matusova et al (2004). The seeds were placed in 2% (v/v) NaOCl to which was added two drops of liquid (hand) soap for 5 min in a beaker.…”
Section: Exudate Collectionmentioning
confidence: 99%
“…gesnerioides seeds Ten milligrams of Striga seeds (approximately 1,500 seeds) was surface-sterilized according to the method of Matusova et al (2004). The seeds were placed in 2% (v/v) NaOCl to which was added two drops of liquid (hand) soap for 5 min in a beaker.…”
Section: Exudate Collectionmentioning
confidence: 99%
“…In order to germinate, seeds of obligate parasitic plants require the presence of the host plant whose roots secrete substances that are perceived by the seed of the parasite and thus stimulate its germination (Bouwmeester et al, 2007;Westwood et al, 2010;Cardoso et al, 2011). For example, in species of Orobanche L. (Plakhine et al, 2012), Phelipanche Pomel (Matusova et al, 2004) and Striga Lour. (Matusova et al, 2004), a very low germination rate (<10 %) has been found in the absence of hosts in all cases.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in species of Orobanche L. (Plakhine et al, 2012), Phelipanche Pomel (Matusova et al, 2004) and Striga Lour. (Matusova et al, 2004), a very low germination rate (<10 %) has been found in the absence of hosts in all cases. The system of chemical recognition assures that germination begins only when the root of the potential host is available in the immediate vicinity (Mohamed et al, 2001;Joel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained by Morozov (1947) established that sunflower root cells contain substances which activate germination of broomrape seeds and in that way support the development of a sprout (stimulators). Long after that, Alonso (1998), Wegmann (1998), Matusova et al (2004) and Höniges et al (2008) also pointed out the importance of broomrape germination stimulants (see 'Overview of its biology and genetics' section for more details). Low exudation of germination stimulants by sunflower roots has been described as a pre-attachment resistance mechanism to race E in the sunflower line LR1, derived from H. debilis subsp.…”
Section: Mechanisms Of Resistance Against O Cumanamentioning
confidence: 99%
“…Orobanche cumana-sunflower co-evolution: A review not stimulated by host roots, seeds enter into secondary dormancy (Matusova et al, 2004). In P. ramosa and O. cumana, it has been demonstrated that seeds need a minimum 4 days conditioning period at 21°C, during which a global DNA demethylation occurs, which is an epigenetic process required for the seed to become responsive to GS (Lechat et al, 2015).…”
mentioning
confidence: 99%